Tourism Experience Effect on Revisit Intention: Trust and Satisfaction in Kintamani: Pengaruh Pengalaman Wisata Terhadap Niat Berkunjung Ulang: Kepercayaan dan Kepuasan Kintamani - Saber, Alexander Barro; Muna, Nilna (Jurnal Ilmiah Hospitality Management, 2024)
This study analyzes the influence of tourism experience on revisit intention, with satisfaction and trust as mediating variables, at the Kintamani tourist destination in Bali. Using questionnaires distributed to 133 tourists who had visited Kintamani and analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS), the research reveals that tourism experience has significant positive effects on revisit intention, satisfaction, and trust. Satisfaction and trust also positively and significantly influence revisit intention, mediating the relationship between tourism experience and revisit intention. Among various aspects of tourism experience, authenticity, hospitality, and service quality are identified as key drivers in building trust and satisfaction. The novelty of this research lies in its exploration of the dual mediating roles of trust and satisfaction, which are often overlooked in previous studies on revisit behavior. It also emphasizes the unique cultural and environmental attributes of Kintamani, offering specific insights for managing similar tourism destinations. The study highlights the urgency of enhancing visitor retention to support Kintamani's economic and cultural sustainability, especially in the face of global tourism challenges. It contributes to the literature by providing an integrated framework for understanding how tourism experiences shape revisit intention through trust and satisfaction. Practically, the research suggests maintaining Kintamani’s natural beauty, improving service quality, providing staff training, and focusing on visitor satisfaction to enhance trust and long-term loyalty. These findings serve as strategic guidelines for sustainable tourism development in Kintamani and similar destinations worldwide.